Clinical Analysis of Ear Congestion after Balloon Eustachian Tuboplasty (BET) with or without Tympanostomy Tube Insertion. (22nd July 2022) - Chen, Nina; Han, Shuguang; Li, Wenjuan; Li, Dong; Hu, Libo; Gong, Shusheng
Abstract : Objective . To explore the clinical analysis of ear congestion after balloon Eustachian tuboplasty (BET) with or without tympanostomy tube insertion. Methods . A total of 35patients (49 affected ears) with ear congestion following BET with or without tympanostomy tube insertion were recruited from the hospitalized patients from January 2015 to December 2017. The score of Eustachian Tube Dysfunction Questionnaire-7 (ETDQ-7) 15, visual analogue scale (VAS), and Valsalva scores were recorded before and after operation, and the influencing factors of prognosis were analyzed. The duration of follow-up was 1–4 years. Results . All patients showed significantly decreased average preoperative ETDQ-7 score, VAS, and Valsalva score after operation (p < 0.05 ). The significance of the surgery types, course of disease, severity of tympanic membrane retraction, and tympanogram tracings classification as influencing factors of prognosis did not come up to the statistical standard (p > 0.05 ). Conclusion . The patients showed relatively stable postoperative conditions after 3 years, and there were variations in the range of ETDQ-7 scores at 5 years postoperatively. Patients with levels I and II tympanic membrane retraction showed more favorable surgical effects. Surgical interventions are required for patients diagnosed with obstructive Eustachian tube dysfunction (ETD) after three months of conservative treatment without satisfactory results.